2021
DOI: 10.1096/fj.202001706rr
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on day‐night differences in cardiac metabolism

Abstract: An intrinsic property of the heart is an ability to rapidly and coordinately adjust flux through metabolic pathways in response to physiologic stimuli (termed metabolic flexibility). Cardiac metabolism also fluctuates across the 24‐hours day, in association with diurnal sleep‐wake and fasting‐feeding cycles. Although loss of metabolic flexibility has been proposed to play a causal role in the pathogenesis of cardiac disease, it is currently unknown whether day‐night variations in cardiac metabolism are altered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 63 publications
1
28
0
Order By: Relevance
“…Though, it is unclear if this would be similar in the vasculature. In relation, time-restricted feeding in alignment with light and dark cycles has been found to partially restore day-night differences in cardiac remodeling, triglyceride synthesis, lipidome, and metabolic flexibility in mice ( Mia et al, 2021 ). Therefore, future work should investigate HFD cessation, as well as time-restricted feeding models on circadian-related genes in the vasculature.…”
Section: Resultsmentioning
confidence: 99%
“…Though, it is unclear if this would be similar in the vasculature. In relation, time-restricted feeding in alignment with light and dark cycles has been found to partially restore day-night differences in cardiac remodeling, triglyceride synthesis, lipidome, and metabolic flexibility in mice ( Mia et al, 2021 ). Therefore, future work should investigate HFD cessation, as well as time-restricted feeding models on circadian-related genes in the vasculature.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that these interventions act through distinct mechanisms and may be combined to achieve an enhanced effect. Ulgherait et al [7] also observed a reduction in markers of ageing in the gut and muscles of Drosophila, and an increase in climbing activity, indicating that iTRF not only increased lifespan, but was also associated with increased healthspan.…”
mentioning
confidence: 95%
“…The authors observed that 30 days of iTRF, from day 10 to day 40 of age, extends lifespan and improves functional capacities in flies. Unlike with other dietary restriction regimens, Ulgherait et al [7] observed that iTRF-induced longevity is independent of calorie restriction, reduction of protein intake, or inhibition of insulin-like signalling. In fact, flies undergoing iTRF combined with dietary protein restriction or inhibition of insulin-like signalling showed a significant additional increase in longevity, similar to the percentage of lifespan increase observed in iTRF alone versus control groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations